Gender, Cultural Memory, and the Representation of Queerness in Ingeborg Bachmann's Narrative "A Step Towards Gomorrah." - Imke Meyer (Studies in 20th & 21st Century Literature, 2007)
This paper explores the questioning of a culturally produced fixed binary gender opposition, as well as of genre conventions, in Bachmann's "Gomorrah." This questioning, I argue, is achieved despite and in part even due to the fact that a lesbian relationship between the text's protagonists remains unrealized. The text's refusal to depict a lesbian relationship is not so much a capitulation to taboos of the 1950's. Rather, it points up the lack of a language and the lack of generic forms that would allow for the representation of true alternatives to traditional gendered power dynamics. If the narrative wants to avoid the reproduction of traditional patriarchal gender relations, it also has to avoid the reproduction of traditional literary forms. Since the narrative cannot speak itself in a form that would represent a viable alternative to traditional genres, it ultimately silences itself in the face of the impossible task of representing a queer relationship. This silence marks a moment of resistance to established cultural norms.
Keywords: gender binary; gender; queer; Gomorrah; Bachmann; lesbian; patriarchy; patriarchal gender relations; Austrian Literature